Fibroblast Growth Factor-1 Improves Insulin Resistance via Repression of JNK-Mediated Inflammation - Fan, Lei; Ding, Linchao; Lan, Junjie; Niu, Jianlou; He, Yiling; Song, Lintao (Frontiers in Pharmacology, 2019)
Insulin resistance is associated with a greatly increased risk of type 2 diabetes. Administration of fibroblast growth factor-1 (FGF-1) resulted in a marked improvement in insulin sensitivity. However, the underlying molecular mechanism whereby FGF-1 represses insulin resistance remains largely unknown. Here, we sought to delineate the role of FGF-1 in insulin resistance with respect to its anti-inflammatory capability. In this study, we found that FGF-1 had positive effects on glucose intolerance, hepatic lipid accumulation and insulin resistance, while it markedly repressed cytokine secretion (TNF-α and IL-6) in serum and reduced liver inflammation in diet-induced obesity (DIO) mice. Further, FGF-1 treatment significantly represses TNF-α-induced insulin resistance in vitro and in vivo. These results indicate that FGF-1 likely ameliorates insulin resistance via a mechanism that is independent of its glucose-lowering activity. Subsequent experiments demonstrated that FGF-1 ameliorated insulin resistance, and inflammation was accompanied by decreased c-Jun N-terminal kinase (JNK) signaling. In addition, it is likely that FGF-1 impedes JNK phosphorylation via blocking the transforming growth factor-β activated kinase 1 (TAK1) and TAK1 binding protein 1 (TAB1) interaction. These findings reveal that FGF-1 regulates insulin sensitivity and may represent an attractive therapeutic target for preventing the development of insulin resistance.